A leadless pacemaker matched with a vasovagal syncope: how long can it last?. (19th May 2022) - Elrefai, M; Abouelasaad, M; Nettey, D; Roberts, P
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Dr.Mohamed ElRefai is receiving an unrestricted grant from Boston Scientific Introduction: Although a benign condition, patients suffering from frequent vasovagal syncopal episodes need treatment to improve their quality of life. ESC Guidelines consider pacing for patients >40 years old with documented symptomatic asystolic pauses >3 seconds or asymptomatic pauses >6 seconds. Caution is advised with use of pacing in younger patients, due to long-term complications associated with transvenous pacemakers (TV-PPM). The ESC guidelines recommend that Leadless pacemakers (LP) should be considered as an alternative to TV-PPM when there is no appropriate venous access or if the risk of device infection is high, also on a case-by-case basis using shared decision making. Studies on the use of LPs for cardioinhibitory vasovagal population specifically, concluded that the safety and efficacy of LPs are comparable with TV-PPM, demonstrating a high level of symptom improvement at follow up making them a reasonable option in these patients. In addition, observational studies demonstrated that LPs are associated with better quality of life than TV-PPM. Purpose: Current practice is to implant another LP after the end of life of the old device without extracting it. There are concerns regards battery longevity specially with the paucity of data on device extraction and the number of concomitant LPs that can be implanted safely, a concern in younger patients' population potentially requiring decades of pacing therapy. We aim to evaluate the performance of the LPs in the relatively younger vasovagal syncope patients with anticipated very low pacing dependency, with emphasis on battery longevity. Methods: We conducted a retrospective analysis of the first 100 LP implanted at our tertiary referral centre for cardiac devices in the UK. Demographical data as well as devices parameters at implant and latest follow ups were obtained from the patients' medical electronic records. We compared the performance of the LPs between patients with vasovagal syncope vs other pacing indications with emphasis on battery longevity in both groups. Results: A total of 90 patients were included in our analysis after excluding 10 patients due to lack of follow-up data. 14 patients (15.6%) had vasovagal syncope as indication for pacing and 76 patients (84.4%) had other indications. Mean ages were 34±13 years and 62±20 years for the vasovagal and the other group, respectively. There were no complications in the vasovagal group. Pacing % at the last follow up was 1±1 in the vasovagal group and 37±43 for the other group. There was a significant difference in the estimated total battery life between both groups, 15.22±0.35 and 13.65±2.97 years in the vasovagal and the other group respectively. Conclusion: LPs provide a safe and a reliable treatment for young patients with vasovagal syncope with promising battery performance at the short/intermediate term. Further longer-term follow up data is needed to identify the true battery potential in this patient cohort.